A low-birth-weight risk assessment scale: development and validation through a questionnaire-based survey - Sonoda, Kazuko; Matsunari, Yuko; Takei, Syuji (BMC Health Services Research, 2019)
Birth weight is continuously decreasing in Japan since food satiation has become a problem in recent years. The present study aimed to develop and examine the reliability and validity of a scale for the assessment of risk factors for low birth weight in infants born at term. A self-administered postal questionnaire survey comprising a low birth weight risk assessment scale was conducted on mothers with children of nursery school or kindergarten age. After item analysis (scale), factor structure was confirmed by an exploratory factor analysis using the main factor method promax rotation. The reliability of this scale was confirmed by Cronbach's α coefficient and Item-Total correlation. The validity was confirmed by known-groups validity and internal validity. The responses of 630 mothers (valid response rate, 18.5%) were analyzed. Factor analysis (principal factor analysis and promax rotation) obtained an optimal scale comprising 25 items in the following nine factors: "guidance at each checkup," "adequate rest," "support from husband," "effects on the fetus," "support from society," "support from family," "effects of minor troubles," "good lifestyle habits," and "fall risk and lifestyle changes." The overall Cronbach's α coefficient for the scale was 0.701. Known-groups validity examination revealed significant differences in scale scores of birth weight, birth history, and maternal smoking status. The scale demonstrated internal consistency, construct validity, and known-groups validity, indicating that it can be used as an indicator of low birth weight risk. In the future, this scale may be included in medical questionnaires as part of health guidance for pregnant women at a risk of delivering low birth weight children.